INTERACTIVE DIGITAL DICTIONARY DEVELOPMENT TO ENHANCE ENGLISH VOCABULARY MASTERY AND READING ABILITY THROUGH SELF-REGULATED LEARNING AMONG JUNIOR HIGH SCHOOL STUDENTS - Rahmi Lira Setyarini, Dewa Ayu Putu; Agustini, Ketut; Sudatha, I Gde Wawan (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
ABSTRACT The rapid expansion of digital technology in English as a Foreign Language (EFL) instruction has generated significant interest in interactive digital dictionaries as tools for vocabulary acquisition and reading development. However, systematic evidence consolidating the effectiveness of such tools across multiple learning outcomes, particularly within the framework of Self-Regulated Learning (SRL), remains limited. This study aims to systematically review empirical literature on the development and effectiveness of interactive digital dictionaries in enhancing English vocabulary mastery, reading ability, and self-regulated learning among Junior High School students (SMP). Following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework, articles were retrieved from three major academic databases: Scopus, Web of Science, and ERIC, using predefined Boolean search strings. Inclusion criteria focused on peer-reviewed journal articles published between 2014 and 2024 that addressed interactive digital dictionaries in EFL contexts with measurable learning outcomes. A total of 1,248 records were initially identified; after screening and eligibility assessment, 45 articles were included for final synthesis. Findings reveal that interactive digital dictionaries, when designed with multimodal features, contextual scaffolding, gamification, and adaptive personalization, significantly enhance vocabulary mastery across breadth, depth, and fluency dimensions. Reading ability improves substantially when digital glossaries are embedded within authentic reading tasks. Self-regulated learning emerges as a critical mediating variable: digital dictionary features supporting goal-setting, self-monitoring, and self-evaluation strengthen learners' regulatory strategies and amplify vocabulary and reading outcomes. Research gaps are identified, including the underrepresentation of secondary school EFL learners, the scarcity of delayed post-test designs, and limited studies from Southeast Asian contexts. This review contributes a synthesized evidence base and design framework for developing interactive digital dictionaries that simultaneously target vocabulary mastery, reading proficiency, and self-regulated learning in Junior High School EFL settings.